Influence of different systems for feeding supplements to grazing dairy cows on milk fatty acid composition. Issue 2 (May 2014) - Akbaridoust, Ghazal; Plozza, Tim; Trenerry, Victor C; Wales, William J; Auldist, Martin J; Dunshea, Frank R; Ajlouni, Said
<x content-type="archive" xml:space="preserve">Abstract</x> This study investigated the effects of different strategies for feeding supplements to grazing dairy cows on the proportions of fatty acids in milk. Two hundred and sixteen cows were fed supplementary grain and forage according to one of 3 different strategies; (1) Control: cows grazed perennial ryegrass pasture (14 kg dry matter/d) supplemented with milled barley grain fed in the milking parlour and pasture silage offered in the paddock; (2) Partial mixed ration 1 (PMR1): same pasture allotment and supplement as Control strategy, but the supplements presented as a mixed ration after each milking in feedpad, and; (3) Partial mixed ration 2 (PMR2): same pasture allotment, supplemented with a mixed ration of milled barley grain, alfalfa hay, corn silage and crushed corn grain fed in a feedpad. Within each strategy, cows were assigned to receive either 6, 8, 10 or 12 kg dry matter supplement/cow per d. Milk fatty acid proportions from cows fed Control and PMR1 strategies were similar and different from those fed PMR2, particularly at 10 to 12 kg dry matter supplement/cow per d. The reduction in milk fat yield and concentration in cows fed high amounts of supplement as Control and PMR1 was coincident with 4 × increase in 10t-18:1 proportion. The composition of the partial mixed ration (PMR) and the amount offered affected milk fatty acid proportions and milk fat content, however, the method of supplementation did not.